2020
DOI: 10.1007/s10648-020-09551-z
|View full text |Cite
|
Sign up to set email alerts
|

Does Touching Real Objects Affect Learning?

Abstract: Based on theories of multimedia learning, the present study investigated whether the haptic sense serves as an additional channel to enhance the learning experience and learning outcomes. We therefore set up an experimental exhibition with two showrooms. In the first showroom, the sensory access of the participants to the exhibition objects was systematically varied in a 2 × 2 design with the between-subjects factors vision and haptics. While one group of participants could touch and see the objects, others co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 76 publications
(136 reference statements)
1
24
0
1
Order By: Relevance
“…Of the 8 studies that surveyed student satisfaction, all reported positive student perceptions. These gains are consistent with objectbased learning (OBL) which hypothesizes that tactile interaction with objects facilitates student learningallowing them to develop their understanding and better visualization concepts [25,26].…”
Section: Introductionsupporting
confidence: 76%
“…Of the 8 studies that surveyed student satisfaction, all reported positive student perceptions. These gains are consistent with objectbased learning (OBL) which hypothesizes that tactile interaction with objects facilitates student learningallowing them to develop their understanding and better visualization concepts [25,26].…”
Section: Introductionsupporting
confidence: 76%
“…As mentioned earlier, the importance of haptic experiences and haptic feedback for learning has been under-researched compared with visual and auditory, but a recent study (Novak & Schwan, 2021) provided some support for the possibility that haptic feedback might improve memory retention. Novak and Schwan's study, in the context of exhibitions of animal husbandry, indicated that the participants who had a haptic experience by touching real objects were able to build a stronger mental representation of the exhibited tools.…”
Section: Haptic Feedback and Learningmentioning
confidence: 98%
“…An additional motivation for this study is to break ground in a largely unexplored area of visualization and physicalization research: the role of touch for making sense of data representations. Research in psychology offers many starting points: people learn to interpret charts by tracing them with their fingers even if they don't offer tactile features [1], touching objects often supports learning and memorizing their features better than just observing them [10,14]. Tactile stimulation is used extensively in the Montessori pedagogy; letters cut from sandpaper help children to learn the alphabet with multiple sensory modalities [14].…”
Section: Touch In Visualization Researchmentioning
confidence: 99%
“…Research in psychology offers many starting points: people learn to interpret charts by tracing them with their fingers even if they don't offer tactile features [1], touching objects often supports learning and memorizing their features better than just observing them [10,14]. Tactile stimulation is used extensively in the Montessori pedagogy; letters cut from sandpaper help children to learn the alphabet with multiple sensory modalities [14]. Also data physicalization research has shown that the ability to touch a tangible data object improves its understanding [11].…”
Section: Touch In Visualization Researchmentioning
confidence: 99%